Characterization of a Rh(iii) porphyrin–CO complex: its structure and reactivity with an electron acceptor1. Issue 31 (21st August 2015) - Yamazaki, Shin-ichi; Yao, Masaru; Asahi, Masafumi; Sato, Hiroyasu; Yamano, Akihito; Ioroi, Tsutomu
<x xml:space="preserve">Abstract</x> To analyse the electrocatalytic oxidation of carbon monoxide by Rh porphyrins, we isolated a CO-adduct of Rh octaethylporphyrin, and examined its properties and reactivity by IR, NMR, and X-ray crystallographic analyses.